Re-Production of Space by Reference to Collective Memory an Urban Design Studio Practice - Özbek Sönmez, İpek; Erin, İrem (ICONARCH International Congress of Architecture and Planning, 2017)
Cities go through changes in time. We may observe some of these spatial changes, however we may not observe the changes in social life of the city, and as time passes we forget. Only if we dig into the memories we come across with the characteristics of the society of the past. We do this exploration from the novels, from the films, photographs or from the memories of the elderly. This paper aims to discuss the outcomes an urban design studio practice where we did examine the history of the city and used the knowledge to re-produce urban space. This discussion firstly will focus on the significance of the knowledge of the past in shaping the future, and these discussions will be carried on the case of Bornova city center where the urban design practice have been experienced. Bornova city center is one of the very special parts of the city of Izmir, where the identity of the Ottoman period settlement, the 19th century Levantine heritage and the modern era spatial pattern can be easily observed. Parallel to the variety of the spatial patterns, the social life at the city had also carried multicultural characteristics and varieties in the time line. This paper will discuss the urban design studio practices of Bornova city center in which various characteristics of city in the time line have been one of the main references in the re-production of the urban space.